Definition of the minimal simian virus 40 large T antigen- and adenovirus E1A-binding domain in the retinoblastoma gene product. - Kaelin, W G (1990)
It has previously been demonstrated that the simian virus 40 large T antigen and adenovirus E1A proteins can form complexes with the retinoblastoma susceptibility gene product (RB). We studied the ability of these proteins to bind to mutant RB proteins in vitro. A region of RB spanning residues 379 to 792 was found to be both necessary and sufficient for binding to T or E1A. Furthermore, this region of RB contains sufficient structural information to mimic wild-type RB in its ability to distinguish between wild-type T and the transformation-defective T mutant K1. The results of competition experiments with peptide analogs of the RB-binding sequence in T suggest that this region of RB makes direct contact with a short colinear region of T, i.e., residues 102 to 115, previously implicated in both transformation and RB binding.